Case Report: Simultaneous chronic lymphocytic leukemia and macrofocal multiple myeloma with extramedullary plasmacytoma - Jin, Yingming; Wang, Shuyan; Fang, Zhi; Qian, Suying (Frontiers in Oncology, 2026)
There are extremely few reports of concurrent multiple myeloma (MM) and chronic lymphocytic leukemia (CLL) in the literature. To the best of our knowledge, the existence of concurrent CLL and macrofocal MM (MFMM), presenting as an extramedullary plasmacytoma (EMP) in a lymph node, has not been previously documented. Herein, we report a case of a 67-year-old male presenting with backache persisting for more than 1 month. Laboratory test results revealed a markedly elevated white blood cell count (57.0 × 109/L) with normal platelet count and hemoglobin level. Positron emission tomography/computed tomography scan showed high fluorodeoxyglucose uptake in the 10th thoracic vertebra (T10), T12, and the left supraclavicular lymph node. Thus, the patient underwent bone marrow aspiration, followed by T10 and left supraclavicular lymph node biopsy. Pathological analysis revealed infiltration by plasmacytoma and neoplastic B-lymphocytes. A final diagnosis of MFMM concurrent with CLL was established. The patient was subsequently treated with bortezomib, lenalidomide, and dexamethasone. After three treatment cycles, a complete response was achieved. However, treatment was discontinued due to grade 3 peripheral sensory neuropathy, and therapy was switched to daratumumab and dexamethasone. The patient remains under outpatient follow-up, with a 1-year follow-up duration.